Tests of the Efficiency of Racetrack Betting Using Bookmaker Odds - Bird, Ron; McCrae, Michael (Management Science, 1987)
The objective of this study is to evaluate the informational efficiency of the market for betting on horse races. Whereas the price data used in previous studies have been drawn largely from totalizator (parimutuel) odds, the data used in this study are derived from bookmaker odds. The availability of a series of prices throughout betting facilitates the use of filter tests to evaluate market efficiency. We conclude that this gambling market is efficient in the use of information supplied via both the movements in odds during the course of betting and the selections of newspaper tipsters. However, there is evidence to suggest that those with access to private information can earn positive returns from gambling.